Earth in the Holy Qur’an: how to protect and maintain it? - Deuraseh, Nurdeng @ Nurdeen (Jabatan Kemajuan Islam Malaysia dan Institut Islam Hadhari, Universiti Kebangsaan Malaysia, 2010)
In order to bring the ummah back to fundamental of Islam, as prescribed in the Qur’an and the Sunnah that form the foundation of Islamic civilization, Islam Hadhari was introduced by the former Prime Minister of Malaysia, Tun Abdullah bin Haji Ahmad Badawi in 2004 based on ten principles of Islam Hadhari. The objective of this paper is to discuss and interpret one of the principle of Islam Hadhari namely The Safeguarding the environment in the light of the Holy Qur’an as well as its role in making a healthy environment by protecting and maintaining the land and soil (earth). In order to fulfill its objective, the relevant verses of the holy Quran will be highlighted with academic interpretations. It is found that the land and soil are considered as essential thing for making a healthy environment. In this regard, the principle of Islam Hadhari namely Safeguarding the environment plays an important role in preservation of the quality of a precious environment. Accordingly, human being was entrusted with a esponsibility not to behave like an unlimited owner, but to live by Divine teachings, with respect to the preservation of ecological balance.